2001
DOI: 10.1038/sj.onc.1204241
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the acidic domain of MDM2 to p53 and MDM2 stability

Abstract: p53 and MDM2 are both degraded by the ubiquitinproteasome pathway. MDM2 binds p53 and promotes its rapid degradation. MDM2 is an E3 ligase that activates self and p53 ubiquitylation. Moreover, MDM2 nuclearcytoplasmic shuttling contributes to p53 degradation in the cytoplasm. We have identi®ed a new region of MDM2 which regulates the stability of both p53 and MDM2. The ®rst 50 amino-acids of the MDM2 acidic domain (222 ± 272) contribute to MDM2 and MDM2-mediated p53 degradation by a mechanism which is independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 64 publications
4
59
0
2
Order By: Relevance
“…There is also data showing that this acidic domain is important for the stability of Mdm2. As reported by Argentini et al (2001), deletion of the acidic domain (residues 222 -272) increases the stability of the protein without decreasing its ubiquitination. Additionally, the interaction site for the amino terminus of p14ARF, which is necessary for p14ARF to increase the levels of Mdm2 and its ubiquitinated forms (Xirodimas et al, 2001a), is also in this acidic region (Midgley et al, 2000;Bothner et al, 2001).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…There is also data showing that this acidic domain is important for the stability of Mdm2. As reported by Argentini et al (2001), deletion of the acidic domain (residues 222 -272) increases the stability of the protein without decreasing its ubiquitination. Additionally, the interaction site for the amino terminus of p14ARF, which is necessary for p14ARF to increase the levels of Mdm2 and its ubiquitinated forms (Xirodimas et al, 2001a), is also in this acidic region (Midgley et al, 2000;Bothner et al, 2001).…”
Section: Discussionmentioning
confidence: 68%
“…Accordingly, Argentini et al (2001) found that LMB partly decreases the export of Mdm2 from the nucleus using heterokaryon assays. However, this is not reflected by any convincing changes in the localisation of Mdm2 in the presence Figure 3 The appearance of the 32 kDa is a post-transcriptional event and is prevented by proteasome inhibitors.…”
Section: Resultsmentioning
confidence: 96%
“…This may be of relevance as the central part of HDM2 is involved in the degradation and ubiquitination of p53 (19,26,27). The central region of HDM2 interacts also with several other proteins that are responsible for p53 regulation, such as L5 (28), L23 (29), L11 (30), p14ARF (31), TBP (32), and Retinoblastoma (Rb) protein (33).…”
Section: Discussionmentioning
confidence: 99%
“…We previously mapped the interaction domain of MDM2 with Vif to aa 168-320, which are located in its central acidic and zinc-finger domains (17). This central domain is different from the primary TP53-binding site located in the N-terminal region, but was recently reported as a second TP53-binding site important for regulation of TP53 stability (23)(24)(25)(26). Interestingly, several proteins, including P300, P14ARF, and pRB, bind to the central domain of MDM2 and regulate the stability and function of TP53 via MDM2 (24,27).…”
Section: Discussionmentioning
confidence: 99%